2018
DOI: 10.1042/bst20170568
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mechanisms of dynein transport in the cytoplasm versus the cilium

Abstract: Two classes of dynein power long-distance cargo transport in different cellular contexts. Cytoplasmic dynein-1 is responsible for the majority of transport toward microtubule minus ends in the cell interior. Dynein-2, also known as intraflagellar transport dynein, moves cargoes along the axoneme of eukaryotic cilia and flagella. Both dyneins operate as large ATP-driven motor complexes, whose dysfunction is associated with a group of human disorders. But how similar are their mechanisms of action and regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 165 publications
(225 reference statements)
0
46
0
5
Order By: Relevance
“…LIS1 is required for cytoplasmic dynein function in many different cell types (Kardon and Vale, 2009;Vallee et al, 2012;. Possibly, it also regulates dynein inside cilia/flagella, where dynactin is absent, since LIS1 is associated with outer-arm dynein required for flagellar beating, and the intraflagella transport dynein-2 is regulated by a philike autoinhibited state (Pedersen et al, 2007;Rompolas et al, 2012;Toropova et al, 2017;Roberts, 2018). Our results on the positive role of LIS1 in dynein activation are consistent with the results that LIS1 enhances the speed and/or frequency of dynein motility to varying extents in different in vitro motility assays in the presence of dynactin and the N-terminal portion of the cargo adapter BicD2 (Baumbach et al, 2017;Gutierrez et al, 2017;Jha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…LIS1 is required for cytoplasmic dynein function in many different cell types (Kardon and Vale, 2009;Vallee et al, 2012;. Possibly, it also regulates dynein inside cilia/flagella, where dynactin is absent, since LIS1 is associated with outer-arm dynein required for flagellar beating, and the intraflagella transport dynein-2 is regulated by a philike autoinhibited state (Pedersen et al, 2007;Rompolas et al, 2012;Toropova et al, 2017;Roberts, 2018). Our results on the positive role of LIS1 in dynein activation are consistent with the results that LIS1 enhances the speed and/or frequency of dynein motility to varying extents in different in vitro motility assays in the presence of dynactin and the N-terminal portion of the cargo adapter BicD2 (Baumbach et al, 2017;Gutierrez et al, 2017;Jha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A mutant dynein with a defect in phi-particle formation was found to accumulate at the centrosome and the spindle pole, suggesting that phiparticle-based autoinhibition plays a role in the intracellular distribution of dynein (Zhang et al, 2017). Interestingly, recent studies have shown that cytoplasmic dynein-2, which is responsible for intraflagellar transport (IFT), forms a phiparticle-like conformation (Toropova et al, 2017;Jordan et al, 2018), suggesting that the formation of phi-particles is a conserved regulatory mechanism of dimeric dyneins (Roberts, 2018). In order to act as a processive motor, the dynein complex needs to interact with other proteins, such as the dynactin complex, as will be explained in the following section on layer 3.…”
Section: Layer 2: Subunit Composition and Integrity Of Dynein Complexmentioning
confidence: 99%
“…In many eukaryotic cells, cytoplasmic dynein is responsible for most of the minus-end directed motion inside the cell (Pfister et al, 2006;Wickstead and Gull, 2007;Kardon and Vale, 2009;Roberts et al, 2013), whereas kinesin is mainly responsible for plus-end directed motion. Cytoplasmic dynein-1 transports several types of cargos, such as vesicles, membranous organelles, mRNA, and viruses (Dodding and Way, 2011;Reck-Peterson et al, 2018), whereas cytoplasmic dynein-2 is responsible for retrograde transport in the cilia and flagella (Hou and Witman, 2015;Roberts, 2018). A striking feature of cytoplasmic dynein-1 is that, despite the wide variety of its function, the heavy chain polypeptide (catalytic subunit) of cytoplasmic dynein-1 is coded in a single gene (Pfister et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIS1 is required for cytoplasmic dynein function in many different cell types (Kardon and Vale, 2009;Vallee et al, 2012;. Possibly, it also regulates dynein inside cilia and flagella where a phi-like state of dynein is present (Pedersen et al, 2007;Rompolas et al, 2012;Toropova et al, 2017;Roberts, 2018). Recent studies have shown that the function of LIS1 is context-dependent (Yamada et al, 2008;McKenney et al, 2010;Huang et al, 2012;Wang et al, 2013;Baumbach et al, 2017;DeSantis et al, 2017;Gutierrez et al, 2017;Jha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%